A Concept of Live Fire Testing to Identify the Aerodynamic Coefficients of a 35 mm Anti-Aircraft Projectile - Leszek BARANOWSKI (Koncepcja badań poligonowych na potrzeby identyfikacji współczynników aerodynamicznych 35 mm pocisku przeciwlotniczego, 2019)
This paper presents a generic algorithm designed to identify aerodynamic coefficients among the data specified in firing tables and projectile flight parameter data recorded during live fire tests. The algorithm and the concept of live fire testing shown here allow developing a mathematical model of projectile trajectory in the form of a modified motion model of a point mass. Potential applications of the model include fire control systems.
Keywords: Identyfikacja współczynników aerodynamicznych 35 mm pocisku przeciwlotniczego